Effects of sintering temperature on physical and mechanical properties of HA/YSZ nanocomposites - Suchittra Inthong (2018)
© 2016 Trans Tech Publications, Switzerland. In the present work, the effects of sintering temperature on physical and mechanical properties of HA/YSZ nanocomposites were investigated. The obtained results have been proved that the sintering temperature contributed greatly to densification and the compressive strength with the highest at 4.80 g/cm3and 74.20 MPa for 80 wt.% of YSZ content in nanocomposites, respectively. The densification increased with increasing sintering temperature, where the compressive strength value was related with densification for the same ratio amount of YSZ. The higher the YSZ contents also significantly produced the ascendant of densification and the compressive strength.